Biological availability of 137Cs and 90Sr in soddy-podzolic soils in the long period of the accident at the Chernobyl NPP - Putyatin, Yury; Tsybulka, Mikalai (Journal of the Belarusian State University. Ecology, 2023)
The content of 137Cs and 90Sr forms in soddy-podzolic automorphic and gleyic soils of different textures (loamy, sandy loamy, sandy) was studied. It has been established that over a long post-accident period, the physical and chemical forms of 137Cs and 90Sr have been transformed in soils, and a dynamic balance has come in their content. 137Cs compounds have undergone non-exchange fixation, and their content in the form available to plants is currently an insignificant fraction – 5–15 %. 90Sr compounds, on the contrary, are predominantly in easily accessible forms, which make up from 60 to 75 % in soddy-podzolic soils, 67 % on average. The transfer factor of 137Cs, depending on the granulometric composition of soils, decreased on average in grain crops by 3.0–6.7 times, in potato tubers – by 5.0–7.5 times. The parameters of 90Sr intake into plants decreased most intensively in the first 1–2 years after the accidental fallout, which was mainly due to the transformation of its water-soluble compounds into exchangeable forms, and over the past 30–36 years they have not practically decreased. Due to the high mobility of 90Sr in the soil, the transfer factor into agricultural crops are significantly higher compared to 137Cs – into grain crops by more than an order of magnitude, into potatoes – by an average of 5 times. Currently, the bioavailability parameters of 137Cs and 90Sr have stabilized and no significant changes are observed. Therefore, based on the current situation and the transfer coefficients of these radionuclides from soil to plants, it can be concluded that the main problems associated with obtaining standard clean crop products can occur on soils contaminated with 90Sr.